2020
DOI: 10.1371/journal.pbio.3000701
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric connections between olfactory bulbs improve odor detection

Abstract: Interhemispheric connections enable interaction and integration of sensory information in bilaterian nervous systems and are thought to optimize sensory computations. However, the cellular and spatial organization of interhemispheric networks and the computational properties they mediate in vertebrates are still poorly understood. Thus, it remains unclear to what extent the connectivity between left and right brain hemispheres participates in sensory processing. Here, we show that the zebrafish olfactory bulbs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 88 publications
1
26
0
Order By: Relevance
“…To explore how the stereotyped behavioral responses to odors relate to their internal representations in the olfactory system, we measured the response of the dorsal olfactory bulb to a subset of stimuli at the same behaviorally relevant concentrations. Patterns of neural activity evoked by different categories of odors are coarsely spatially organized in the ventral parts of the zebrafish olfactory bulb [6,11,14,65,66]. On the dorsal olfactory bulb, we found that bile acids strongly activated the medial parts, in accordance with previous studies in juvenile zebrafish [12].…”
Section: Neural Representation Of Behaviorally Relevant Odorssupporting
confidence: 90%
See 3 more Smart Citations
“…To explore how the stereotyped behavioral responses to odors relate to their internal representations in the olfactory system, we measured the response of the dorsal olfactory bulb to a subset of stimuli at the same behaviorally relevant concentrations. Patterns of neural activity evoked by different categories of odors are coarsely spatially organized in the ventral parts of the zebrafish olfactory bulb [6,11,14,65,66]. On the dorsal olfactory bulb, we found that bile acids strongly activated the medial parts, in accordance with previous studies in juvenile zebrafish [12].…”
Section: Neural Representation Of Behaviorally Relevant Odorssupporting
confidence: 90%
“…The alarm odors, skin extract and conspecific blood, activate spatially overlapping olfactory bulb domains Our behavioral data suggest that zebrafish can smell blood and exhibit defensive behaviors that are similar to responses induced by the commonly used alarm odor, skin extract. To investigate whether conspecific blood activates the zebrafish olfactory system, we measured olfactory bulb responses to a subset of our odors, using two-photon calcium imaging in a brain explant preparation of Tg(elavl3:GCaMP6s) adult zebrafish [6,11,41,42] (see the "Methods" section). We found that both blood and skin extract specifically activated a subset of olfactory bulb neurons located in the anterolateral domain, below the dorsal surface of the olfactory bulb (Fig.…”
Section: Categorization Of Odors Based On Behavioral Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that zebrafish MCs receive direct interhemispheric projections from their contralateral counterparts, whereas interneurons receive interhemispheric top-down inputs from the contralateral zebrafish homolog of the olfactory cortex (Kermen et al, 2020). Mouse MCs/TCs receive indirect interhemispheric projections from their contralateral counterparts via the anterior olfactory nucleus pars externa (Grobman et al, 2018), whereas interneurons receive top-down inputs mostly from the ipsilateral olfactory cortex (Niedworok et al, 2012).…”
Section: The Function Of 5t4 In a Granule Cell Subtype Within The Olfmentioning
confidence: 99%